Multi-proxy evidence of Late Quaternary environmental changes in the coastal area of Puerto Lobos (northern Patagonia, Argentina) - Boretto, Gabriella Margherita (2013)
A multidisciplinary approach involving geomorphology, taxa composition of mollusks and taphonomy performed on bivalve shells, linked to mineralogical and microstructural analyses, provide evidence of Late Quaternary environmental changes in the coastal area of Puerto Lobos, in northern Patagonia. Digital elevation models (DEMs) showed a beach ridge system developed parallel to the coast, indicating sea level variations during MIS1, MIS5e, and earlier in the Pleistocene. These ridges can be correlated with other marine ridges along the Patagonian coast, showing a similar geomorphological pattern and similar temporal evolution. In relation to faunal composition, when comparing the Pleistocene with the Holocene, the most relevant differences are the presence of Tegula atra and Mactra patagonica in the Pleistocene sediments and a diversification of taxa in the Holocene. During the late Holocene, the coastal area of Puerto Lobos also recorded a faunal shift in which species belonging to the Magellan Province displaced the fauna of the Argentinean Province to the north, probably in coincidence with the Little Ice Age (LIA). Taphonomic analysis on Glycymeris longior and Venus antiqua shells, two common taxa in these beach ridges, indicate greater energy in the depositional environment correlated with the youngest Holocene beach ridge. These shells exhibited taphonomic differences between them in relation to fracturing, explained on the basis of higher elasticity in the G. longior shell than in V. antiqua shell, because of its crossed lamellar microstructure.